Artificial Emasculation and the Maintenance of a Masculine Identity in Professional Hockey - Robidoux, Michael (Ethnologies, 1997)
This article is an exploration of the construction of masculinity within professional hockey culture, and how this closed environment perpetuates an artificially secure gender identity. Despite the illusion of security provided by this male preserve, it is an inherently discriminatory group that is intolerant of difference, subsequently forcing players to either conform to existing norms, or be completely ostracized. The field research for this project consisted of random interviews held with hockey players in the spring of 1996, and a six month ethnography of a professional hockey team conducted in the 1996-1997 hockey season.